Analisis Kemampuan Numerasi Siswa SMP dalam Menyelesaikan Soal Kontekstual Materi Bilangan - Hanipa Hanipa; Duano Sapta Nusantara; Fiki Alghadari; Da Tien Nguyen (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2026)
The numeracy skills of students in Indonesia are expected to be at a level that supports contextual problem-solving and higher-order thinking. However, international assessment results indicate that the numeracy skills of Indonesian students remain in the low category and have not yet met expected standards, as reflected in the 2022 PISA results, in which Indonesia achieved an average score of 366 points in mathematics well below the OECD average of 472 points. This study aims to analyze the numeracy ability of junior high school (SMP) students based on three cognitive domain indicators: Understanding (U), Applying (A), and Reasoning (R). A descriptive quantitative approach was employed with 32 students selected through purposive sampling. Data were collected through a written test consisting of 6 items with a maximum score of 72 points, supplemented by semi-structured interviews. Results indicate that the average numeracy score was 30.34%, classified as Low. No student reached the High or Very High category; 56.25% of students were in the Low category. Per-indicator analysis revealed a consistent decline from Understanding (38.80%), Applying (27.21%), to Reasoning (25.00%). Item 1a had the highest achievement rate (93.75%), while item 2c could not be answered by any student (0.00%). These findings indicate the urgent need for authentic context-based learning that fosters higher-order thinking skills at the junior high school level.